Fisheries oceanography (Cambridge, MA, 1995)
Why some marine fish are super abundant and attract the attention of commercial fisheries is a question which can only be fully addressed by looking not only at biological aspects, such as reproduction and population dynamics, but also at the surrounding oceanic conditions by analyzing physical, chemical, geomorphological and other data.
Keywords: Fishery oceanography,Hảỉ dương học nghề cá